Interaction between the Conjugated Polyelectrolyte Poly{1,4-phenylene[9,9-bis(4-phenoxybutylsulfonate)]fluorene-2,7-diyl} Copolymer and the Lecithin Mimic 1-O-(l-Arginyl)-2,3-O-dilauroyl-sn-glycerol in Aqueous Solution - Tapia, María J. (2006)
In this paper, the interaction between the water-soluble conjugated polyelectrolyte poly{1,4-phenylene[9,9-bis(4-phenoxybutylsulfonate)]fluorene-2,7-diyl} copolymer and the amino acid glyceride conjugate 1-O-(l-arginyl)-2,3-O-dilauroyl-sn-glycerol dichlorohydrate (a mimic for the phospholipid lecithin) has been studied in aqueous solution by electronic spectroscopy (absorption and fluorescence) and small-angle neutron scattering (SANS). A significant increase in the polymer fluorescence and blue shift in its emission are observed on association with the surfactant. This is suggested to be due to breakup of polymer aggregates. In addition, the spectroscopic and photophysical data suggest this is followed by the vesicle to ribbon transition characteristic of this surfactant, leading to incorporation of single chains of the polymer within mixed polymer−surfactant aggregates. Support for this comes from preliminary SANS measurements, from which evidence for polymer dissolution and formation of two-dimensional structures has been obtained.